The VIDIA BONE score as a patient- and fracture-related risk score for the occurrence of fracture sequelae in proximal humerus fractures - Kimmeyer, Michael; Liebherr, Norbert; Schmalzl, Jonas; Rentschler, Verena; Gerhardt, Christian; Lehmann, Lars (BMC musculoskeletal disorders, 2024)
The aim of the study was to determine preoperative patient- and fracture-related risk factors for estimating the risk of fracture sequelae after surgically treated proximal humerus fractures (PHF) using locking plate osteosynthesis. The purpose was to develop a fracture sequelae risk score as an additional tool to facilitate the treatment strategy for PHF. All patients with PHF who underwent surgery with locking plate osteosynthesis were included. Inclusion criteria were complete preoperative parameters including general patient-specific information, preoperative radiographs and computed tomography (CT) scans. The patients were divided into 2 groups according to the occurrence of fracture sequelae (Group I: no fracture sequelae, Group II: fracture sequelae). Following risk factors for fracture sequelae were defined: Vascular supply interruption risk [V], Individual (female gender) [I], Diabetes [D], ISAR (Identification of Seniors at risk) [I], ASA (American Society of Anesthesiologists) score [A], Body mass index [B], Osteopenia [O], Nicotine abuse [N], Elderly > 65 [E]. The VIDIA BONE score contains 9 items. For each parameter of the VIDIA BONE score, a value between 1 and 3 was assigned based on the odds ratio (OR). This comparative case series study included 112 patients, with 82 (73.2%) in Group I and 30 (26.8%) in Group II. All defined preoperative risk factors were associated with an increased risk of fracture sequelae (FS), with odds ratios (OR) ranging from 1.3 to 3.9, although not all parameters reached statistical significance. The maximum score was 24 points, categorized as follows: scores of 1 to 8 indicating low risk, 9 to 16 indicating moderate risk, and 17 to 24 indicating high risk of fracture sequelae following PHF. Patients with a VIDIA BONE score of 1 to 8 points demonstrated favorable postoperative outcomes, with FS observed in only 6% of cases. In contrast, 84% of patients with a score of 17 to 24 developed a FS. Additionally, 90% of all patients who developed FS had a VIDIA BONE score more than 9 points. The VIDIA BONE score appears to be a simple, reproducible, and valuable tool for supporting reliable treatment decisions. Locking plate osteosynthesis is an effective treatment option for patients with a low risk VIDIA BONE score. However, patients with a high risk VIDIA BONE score are more likely to experience FS and osteosynthesis failure. III.
Gesehen am 10.04.2025